The rise of modern China - Hsü, Immanuel C. Y. (Immanuel Chung-Yueh) 1923-2005 (Oxford University Press, 2000)
This text covers Chinese history since the 17th century and analyzes the return of Hong Kong and Macao. The author also explores China's emergence as a regional and global superpower, Chinese-American rivalry and the unification with Taiwan.